Globalization and player recruitment: How teams from European top leagues broker migration flows of footballers in the global transfer network - Velema, T. A. (International Review for the Sociology of Sport, 2021)
Theories about how Europe`s clubs drive the global migration of football players argue that teams recruit in culturally similar and historically linked countries, in global value-added chains, or in their home country and abroad in far-flung countries. However, most of these theories on club behavior are empirically thin, because researchers have so far analyzed stocks of players in teams rather than flows of players between teams. To understand how teams drive the globalization of football`s labor market, this study uses social network analysis to examine how teams from Europe`s top eight leagues broker the global transfer network encompassing 1700 professional clubs in 82 countries. Results demonstrate that European elite teams do not scout globally, but rather recruit from rivals in European top leagues. Clubs one tier below the elite hire both in their home country and across European and Latin-American leagues. The majority of European teams focus their recruitment on their home country and occasionally hire from neighboring countries. How teams recruit in the global transfer market might thus be better understood through the interplay between the risky business of hiring players and the resources teams have at their disposal.